Peripheral Contributions to Visceral Hyperalgesia - GF Gebhart (Canadian Journal of Gastroenterology)
Hyperalgesia has long been recognized clinically as a consequence of tissue injury. Primary hyperalgesia (arising from the site of injury) is generally considered to be due to sensitization of sensory receptors (eg, nociceptors) and perhaps activation of so-called ‘silent nociceptors’ by mediators released, synthesized or attracted to the site of tissue injury. Key questions associated with understanding visceral hyperalgesia relate to whether the viscera are innervated by nociceptors (ie, sensory receptors that respond selectively to noxious intensities of stimulation), whether visceral receptors and/or afferent fibres sensitize after tissue injury and whether silent nociceptors exist in the viscera. Studies in nonhuman animals have revealed that hollow organs such as the esophagus, gall bladder, stomach, urinary bladder, colon and uterus are innervated by mechanically sensitive receptors with low or high thresholds for response. Accordingly, it appears that the viscera are innervated by nociceptors, although the issue is far from settled. One characteristic of cutaneous nociceptors is their ability to be sensitized when tissue is injured. Mechanosensitive visceral receptors also sensitize when the viscera are experimentally inflamed, but both visceral receptors with low thresholds and those with high thresholds for response are sensitized. Moreover, it is often not appreciated that visceral receptors are likely polymodal rather than unimodal – that is, mechanically sensitive visceral receptors typically are also sensitive to chemical and/or thermal stimuli. In this sense, visceral receptors may be considered evolutionarily older than more highly developed, specialized cutaneous receptors. Finally, there are mechanically insensitive receptors that innervate the viscera and, when tissue is injured, develop spontaneous activity and acquire sensitivity to mechanical stimuli. In the aggregrate, visceral receptors change their behaviour in the presence of tissue injury and, along with activated mechanically insensitive receptors, increase the afferent barrage into the spinal cord, contributing to the development of visceral hyperalgesia.